The powers of preservation new life for urban historic places - Moore, Arthur Cotton 1935- (McGraw-Hill, 1998)
Moore draws upon more than three decades of professional experience and his enormous portfolio of large-scale rehabilitation projects to show how preservation, by embracing a wider range of historic buildings and a looser attitude toward contextual design, can remedy the visual chaos and economic divestment that now characterize our cities." Includes a brief mention of his work in Charleston, South Carolina, on the Cathedral of St. John the Baptist and on the waterfront warehouse renewal.